2005
DOI: 10.2320/matertrans.46.1088
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Phenomena in Metals with Electric and Magnetic Fields: II Magnetic Fields

Abstract: Magnetic field effects were first noticed in texture formation in ferrous alloys more than half a century ago, when the available field intensity was an order of or less than one Tesla. With increasing availability of very intense magnetic fields of an order of ten Tesla, the potential of magnetic field as an additional controllable external parameter for microstructure control is widely recognized, not only in ferromagnetic, but also in non-ferromagnetic metals and alloys. As a companion paper to Part I on el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…Researchers have paid many attentions to reveal the relationship between high magnetic field and the recrystallization behavior of the deformation alloys. Most researches in this field are related to magnetically affected recrystallization in ferromagnetic materials [1][2][3]. With the development of high magnetic field technologies, researchers found that non-ferromagnetic metals which almost have no reaction in the conventional magnetic field heat treatment are also quite sensitive under the high magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have paid many attentions to reveal the relationship between high magnetic field and the recrystallization behavior of the deformation alloys. Most researches in this field are related to magnetically affected recrystallization in ferromagnetic materials [1][2][3]. With the development of high magnetic field technologies, researchers found that non-ferromagnetic metals which almost have no reaction in the conventional magnetic field heat treatment are also quite sensitive under the high magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Watanabe et al [14,15] wrote review papers on grain boundary engineering by magnetic field application and Enomoto [16] published a review paper on the enhancement of phenomena in metals by applying magnetic fields. Several review papers have also been published by the author [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In this field, much progress has been made regarding textural orientations, phase transformations, solidifications and interfacial reactions (Ajayan and Tour, 2007;Asai et al, 2003;Enomoto, 2005;Wang et al, 2007;Ren et al, 2006;Nakamichi et al, 2005). As we know that many processing techniques, e.g.…”
Section: Introductionmentioning
confidence: 98%